ANALISIS RENCANA STRATEGIS PENGEMBANGAN PARIWISATA KABUPATEN TULUNGAGUNG - Wahyu Bhudianto, Badra Sugara, Suwardi & (Transformasi, 2016)
This research aims to describe and find out about tourism development strategic plan analysis ofTulungagung district. According to the SWOT analysis that is conducted by the author the mostappropriate strategy in developing tourism Tulungagung district is ST strategy that use itsstrength that exists to face the threats. The results of the analysis of the strategic plan(RENSTRA) of the Ministry of culture, tourism, youth and sports Tulungagung district 2014-2018 shows that the contents of the corresponding right to what Renstra mandate PP number 8in 2008. But there is no strategy in more detail.The authors conclude that the potential of tourism exists in Tulungagung, the most numerous andhas most potential is the Nature tourism sector as well as Cultural tourism. To establish thetourism development in Tulungagung it is suggested to use strategies ST (Strength-Threat).Direction of the tourism development in Tulungagung district, is establishing Tulungagung as aviable tourist destination selling and contribute to the economy and the welfare of society.Keyword: Strategic, Development, tourism, Tulungagung